Why the command-and-control style of management is no longer useful - V Basil Hans (Journal of Advanced Research in Economics and Business Management, 2026)
Command-and-control management used to work well in stable and predictable settings, but it is becoming less and less useful in today’s fast-paced, knowledge-driven businesses. This essay contends that inflexible hierarchies, centralised decision-making, and top-down authority impede adaptability, creativity, and employee engagement in contemporary companies. As work gets more complicated and requires more teamwork, managers can’t rely on control as the main way to get things done. Instead, successful companies are moving towards leadership based on trust, decision-making that is spread out, and teams that have more power. Based on modern management theory and real-world business practices, the essay looks at why command-and-control methods don’t work for long-term success and suggests some practical alternatives for leaders who want to make their organisations more flexible, accountable, and productive over time. In the end, it changes the manager’s job from making sure everyone follows the rules to helping them grow and learn.